Pembelajaran Literasi Saintifik untuk Pendidikan Dasar - Adib Rifqi Setiawan; Wahyu Eka Saputri (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
This research constructs a learning design to guide primary students on achieving scientific literacy. The approach used is a mixed-method sequential exploratory model. This result shows that the validity and reliability of this design in general on the category can be used. The implementation of 35 students in Kabupaten Kudus revealed that this design could be applied by the teacher and could be responded to by students during learning.